The prevalence and causes of visual impairment among children in Kenya – the Kenya eye study - Shadrack Muma; Stephen Obonyo (BMC Ophthalmology, 2020)
Abstract Background Visual impairment is the partial or complete loss of vision in which the presenting visual acuity lie between 6/18-no perceptions of light. In Kenya, little attention has been directed towards children vision and causes of visual impairment. Therefore, this study was designed to investigate the prevalence and causes of visual impairment in the children population of Kenya. Methods This cross-sectional population-based study included 3400 (1800, 52.9% female) randomly selected children with a mean age of 12 ± 2 years (range 5–16 years). Visual acuity was taken using Snellens chart at 6 m. Anterior and posterior segment was assessed using slit lamp and indirect ophthalmoscope. The World Health Organization definition formed the baseline for calculating the mean prevalence of visual impairment. Results Visual acuity measurements were available for 3240 (95.3%) participants. The mean prevalence of visual impairment based on pin-hole value was 1.7 ± 0.3% using World Health Organization definition. The prevalence of visual impairment based on presenting visual acuity value was 2.4 ± 0.7% using the World Health Organization definition. Multivariate analysis demonstrated that the presence of visual impairment on pin-hole increased significantly with increasing age (odds ratio 1.230, P = .021) and uncorrected refractive error (odds ratio 0.834, P = .032) according to World Health Organization definition. Cases of uncorrected refractive error remained the major cause for presenting visual impairment. Causes of visual impairment due to presenting visual acuity were nystagmus (14%), amblyopia (24%) and uncorrected refractive error (62%). Conclusion The prevalence of visual impairment in Kenya is associated with age. Uncorrected refractive error remains the major causes of visual impairment.